PENGARUH EFIKASI DIRI, ETOS KERJA, DAN DUKUNGAN ORGANISASI YANG DIRASAKAN TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH PROVINSI BANTEN - Ade Jaya Sutisna; Nisa Agustina (Universitas La Tansa Mashiro, 2022)
This study aims to determine the effect of self-efficacy, work ethic, and perceived organizational support on employee performance. The research method used is descriptive-verificative quantitative method. Analysis of the data used is multiple linear regression. Data were collected using a questionnaire distributed to 91 respondents. The research population was all employees of the Banten Province Regional Secretariat, totaling 1002. The research sample was taken by proportional random sampling with Slovin's calculation, as many as 91 respondents. The results obtained: (a) there is an influence of discipline on employee performance as indicated by the results of the t-test, which is obtained t-count of 8,210 with a significance value (p-value) of 0.000, (b) there is an influence of work ethic on the performance of Secretariat employees. Banten Province, indicated by the t-count value of 4,409 with p-value = 0.001, (c) there is an influence of perceived organizational support on the performance of the Banten Provincial Secretariat employees, indicated by the t-count value of 4,832 with a p-value = 0.000, and (d) there is a simultaneous effect of self-efficacy, work ethic, and organizational support on the performance of the Banten Provincial Secretariat employees, indicated by the F-count value of 131,622 with a significance value (p-value) of 0.000 . The implication of this study is to improve employee performance at the Banten Provincial Secretariat Office, it can be done through increasing employee self-efficacy, employee work ethic, and organizational support felt by the employees. The suggestion that the author conveys is that the Banten Provincial Secretariat Office should improve the performance of its employees, namely by paying more attention to employee self- efficacy, increasing employee work ethic, and positive organizational support felt by employees.